Fruit and Fruit-Derived Products of Selected Sambucus Plants as a Source of Phytosterols and Triterpenoids - Otgonbileg Onolbaatar; Soyol Dashbaldan; Cezary Pączkowski; Anna Szakiel (Plants)
Plant-derived foods have gained recognition for their health-promoting values, which are largely attributed to bioactive compounds such as phytosterols and triterpenoids. This study aimed to analyze the content of these compounds in the fruit of black elder (elderberry) Sambucus nigra L. and in commercially available food products, including jam, juice, syrup and wine. An additional objective was to compare the phytosterol and triterpenoid profiles of fruits and fruit cuticular waxes from wild and cultivated elderberry (cultivar Haschberg), ornamental elderberry (S. nigra f. porphyrophylla cultivar Black lace “Eva”), and red elderberry (S. racemosa). Qualitative and quantitative determinations were performed using gas chromatography coupled with mass spectrometry (GC-MS). This study provides a detailed characterization of triterpenoids in black and red elderberries, revealing a complex composition of oleanane-, 18-oleanane-, ursane-, lupane- and taraxastane-type compounds. Elderberry fruits were found to be rich sources of phytosterols (ranging from 0.54 mg/g d.w. in cultivated elderberry cv. Haschberg to 0.96 mg/g in ornamental elderberry) and triterpenoids (from 1.41 mg/g d.w. in S. racemosa to 13.81 mg/g in ornamental elderberry). Among the processed products, jam contained the highest concentration of these compounds (a total of 340 µg/g) and wine contained the lowest (0.87 µg/mL). Furthermore, the results suggest that certain features of the triterpenoid profile in S. nigra and S. racemosa may hold chemotaxonomic significance for the Sambucus genus.